Pengaruh Pengungkapan ESG, Kinerja Lingkungan, dan Biaya Lingkungan terhadap Net Profit Margin (NPM) pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2022–2024 - Mariska Putri Tarigan; Fitrini Mansur; Muhammad Gowon (Jurnal Riset Akuntansi, 2026)
This study aims to determine the effect of ESG Disclosure, Environmental Performance, and Environmental Costs on the Negative Net Profit Margin (NPM) of Energy Sector Companies Listed on the Indonesia Stock Exchange for the 2022-2024 Period. The data used in this study consists of secondary data obtained from annual reports and company sustainability reports. The analysis tool used is SPSS 31 software to view the results partially and simultaneously. The results show that ESG Disclosure does not affect Net Profit Margin (NPM). Likewise, environmental performance does not show a effect on Net Profit Margin (NPM). Meanwhile, environmental costs show an negative effect on Net Profit Margin (NPM). Simultaneously, ESG disclosure, environmental performance, and environmental costs have a negative effect on Net Profit Margin (NPM). The results show that when environmental costs are high, the Net Profit Margin (NPM) value decreases, and vice versa. Meanwhile, ESG disclosure and environmental performance do not have a significant impact on Net Profit Margin (NPM). This research contributes to company management and stakeholders in understanding the impact of environmental costs on profitability as reflected in the Net Profit Margin (NPM) return on assets ratio and provides insight in decision making.